(untitled) (Vietnam Journal of Community Medicine, 2026)
Backgrounds: Tpeak-Tend interval and Tpeak-Tend/QT ratio were electrocardiographic markers of ventricular repolarization dispersion and arrhythmic risk. However, their diagnostic value for heart failure in patients with hypertension remains controversial. Objectives: To evaluate the diagnostic value of the Tpeak-Tend interval and Tpeak-Tend/QT ratio in diagnosis heart failure in patients with hypertension. Subjects and methods: A cross-sectional study including 109 hypertensive patients treated at the Vietnam National Heart Institute, Bach Mai Hospital, from December 2022 to October 2023. Among them, 79 patients had heart failure and 30 did not. Standard 12-lead electrocardiograms were analyzed to measure Tpeak-Tend and QT intervals using the tangent method. The Tpeak-Tend/QT ratio was calculated for precordial leads V1–V6. ROC analysis was performed to evaluate the diagnostic performance. Results: Patients with heart failure had significantly prolonged Tpeak-Tend across all precordial leads compared with those without heart failure (mean V1–V6: 87.30 ± 9.01 ms vs. 77.21 ± 6.83 ms, p < 0.001). The QT interval did not differ significantly between groups (p > 0.05). The Tp–Te/QT ratio was also significantly higher in the heart failure group (0.218 ± 0.023 vs. 0.199 ± 0.024, p < 0.001). ROC analysis demonstrated good diagnostic performance of Tpeak-Tend (AUC = 0.811) and fairly good diagnosis performance of Tpeak-Tend/QT (AUC = 0.709). The optimal cut-off values were ≥ 79.16 ms for Tp–Te (sensitivity 86.1%, specificity 63.3%) and ≥ 0.209 for Tpeak-Tend/QT (sensitivity 69.6%, specificity 73.3%). Conclusions: In hypertensive patients, the Tpeak-Tend interval and Tpeak-Tend/QT ratio are significantly increased in those with heart failure. Tpeak-Tend demonstrates good diagnostic value, while Tpeak-Tend/QT shows acceptable performance. These repolarization dispersion markers may serve as useful adjunct electrocardiographic tools for heart failure detection in hypertensive populations.